2020
DOI: 10.18632/aging.103023
|View full text |Cite
|
Sign up to set email alerts
|

DNA N6-methyladenine modification in hypertension

Abstract: DNA methylation has a role in the pathogenesis of essential hypertension. DNA N6-methyladenine (6mA) modification as a novel adenine methylation exists in human tissues, but whether it plays a role in hypertension development remains unclear. Here, we reported that the global 6mA DNA level in leukocytes was significantly reduced in patients with hypertension and was reversed with successful treatment. Age, systolic blood pressure, and serum total cholesterol and high-density lipoprotein levels were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…The blood pressure of CKD patients showed difference between Non-VC and VC group (Table 1). In addition, ALKBH1 was associated with hypertension (19). However, we found systolic blood pressure, diastolic blood pressure, and other parameters including blood glucose, cholesterol, and triglyceride were not affected by ALKBH1 deficiency or overexpression in vivo (Supplemental Table 1-3, Supplemental Figure 7).…”
Section: Overexpression Of Alkbh1 Enhances Vascular Calcificationmentioning
confidence: 76%
See 2 more Smart Citations
“…The blood pressure of CKD patients showed difference between Non-VC and VC group (Table 1). In addition, ALKBH1 was associated with hypertension (19). However, we found systolic blood pressure, diastolic blood pressure, and other parameters including blood glucose, cholesterol, and triglyceride were not affected by ALKBH1 deficiency or overexpression in vivo (Supplemental Table 1-3, Supplemental Figure 7).…”
Section: Overexpression Of Alkbh1 Enhances Vascular Calcificationmentioning
confidence: 76%
“…Several studies revealed that there is a robust relationship between ALKBH1demethylated DNA 6mA modification and cardiovascular diseases, such as hypertension and atherosclerosis (18,19). As previously reported, ALKBH1-mediated 6mA demethylation is required for the osteogenic differentiation of human mesenchymal stem cells during bone metabolism (20).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The enrichment of certain fragments was determined using real-time PCR. The enrichment of the RNAs was normalized to inputs from the siRNA control group [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The senescence of vascular cells promotes arterial stiffness, causing hypertension (Qiu et al, 2010;Chi et al, 2019). DNA methylation is involved in hypertension (Gao et al, 2018;Guo et al, 2020;Amenyah et al, 2021). Kazmi et al investigated the relationship between hypertension and DNA methylation in European men and discovered that 7 CpG sites were related to diastolic blood pressure (Kazmi et al, 2020).…”
Section: Hypertensionmentioning
confidence: 99%